Allele frequencies of 31 autosomal short tandem repeat (auSTR) loci obtained using the Precision ID GlobalFiler™ NGS STR Panel v2 in 322 individuals from the Japanese population. (November 2022) - Ohuchi, Tsukasa; Guan, Xueting; Hirai, Eriko; Hashiyada, Masaki; Manabe, Sho; Akane, Atsushi; Adachi, Noboru; Tamaki, Keiji; Funayama, Masato
Highlights: A Japanese database of 31 STR loci was constructed from 322 individuals using MPS. The match probability for sequence-based data was 9.163 × 10 −38 . Attention should be paid to sequencing errors and allele drop-out for practical use. Abstract: In human identification methods that target short tandem repeats (STRs), massively parallel sequencing (MPS) technology has made it possible to genotype at the level of the specific sequence itself. This allows for the detection of repeat unit variants and single nucleotide polymorphisms (SNPs) adjacent to the STRs. Using the GlobalFiler™ NGS STR Panel v2, Ion S5, and Converge software, this study constructed a Japanese database of 31 autosomal STRs (auSTRs) and two sex markers from 322 individuals. After excluding some sequence errors and stutters, a total of 31 novel alleles were identified. Additionally, using the allele frequencies of 31 auSTR loci, the match probabilities for the length-based and sequence-based data were calculated to be 1.433 × 10 −34 and 9.163 × 10 −38, respectively. These values are at least nine orders of magnitude higher than that obtained from 21 auSTR loci in the Japanese population using the conventional capillary electrophoresis method. The database generated in this study is expected to be implemented in forensic practice and used to solve difficult casework.